Spatial organization, chromatin accessibility and gene-regulatory programs defining mouse sensory neurons - Doris Krauter; Jussi Kupari; Dmitry Usoskin; Jie Su; Yizhou Hu; Ming-Dong Zhang; Patrik Ernfors (Communications Biology)
Abstract Heterogeneity among somatosensory neurons is necessary for internal and external sensation. Precise patterns of gene transcription orchestrated through enhancer activation maintain heterogeneity. Thus, high-resolution cell type classification, chromatin accessibility and its relation to enhancer activation can explain the governing principles for sensory neuron heterogeneity. Here, we present an integrated atlas from published high-quality scRNA-seq datasets and resequencing the dorsal root ganglion, including over 44,000 neurons. MERSCOPE spatial transcriptomics confirms cell types in situ, including previously unrecognized neuronal types, and a spatial zonation of both neurons and non-neuronal cells. We present a cell type specific open chromatin atlas revealing enhancer driven regulons and gene-regulatory networks organized into co-regulated gene-programs that together define sensory neuron diversity. Cell type complexity is shown to be generated by layered co-regulated transcriptional modules representing shared functions across different scales of the neuronal type hierarchy with cell type specific contribution as the exception.